The Influence of Self-Esteem and Self-Efficacy on Employee Job Satisfaction (Case Study of MSMEs in Palopo City) - Yesi; Muhammad Kasran; Samsinar (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the influence of self-esteem and self-efficacy on employee job satisfaction (case study on MSMEs in Palopo City). Quantitative methods were used with a population consisting of MSME employees in Palopo City. A sample of one hundred and fifty employees was selected using a purposive sampling technique. The analysis was conducted using Structural Equation Modeling (SEM) and Partial Least Squares (PLS-SEM) with Smart PLS 4. The results of the study indicate that (1) self-esteem and self-efficacy play a major role in influencing employee job satisfaction in MSMEs in Palopo City. (2) Employees who feel valued and confident in their abilities tend to be more satisfied, more motivated, and experience lower stress levels. (3) These findings indicate that MSME owners can improve employee job satisfaction by providing training, rewards, and career development opportunities. In addition, this research can also serve as a reference for policy makers in designing regulations that support the welfare of MSME workers and increase the competitiveness of small businesses.